2019
DOI: 10.6018/cpd.348611
|View full text |Cite
|
Sign up to set email alerts
|

Gender (In)equality: A Longitudinal Analysis of Women's Participation in Coaching and Referee Positions in the Brazilian Women’s Basketball League (2010-2017)

Abstract: The aim of this study was to analyze the participation of women in coaching and referee positions in the Brazilian Women’s Basketball League, from the first edition of the championship (2010) to the present moment (2017). For this proposal, we analyzed the gender of the coaching staff and referee crews from all the matches played in this period. All data were collected from the official match reports, accessed at the League headquarters. The results showed that women represent 24% of the head coaches, and this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
2
3
0
9
Order By: Relevance
“…In this case, it can be said that women need more to prove themselves not only in coaching but also in refereeing in sport than male individuals. The literature has the studies on that lack of female role models can discourage young girls from following the leadership positions in sport (Passero et al, 2019;Walker and Bopp, 2010). This result corresponds to the findings of the study on female refereeing in karate.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In this case, it can be said that women need more to prove themselves not only in coaching but also in refereeing in sport than male individuals. The literature has the studies on that lack of female role models can discourage young girls from following the leadership positions in sport (Passero et al, 2019;Walker and Bopp, 2010). This result corresponds to the findings of the study on female refereeing in karate.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, 43.6% emphasized the numerical scarcity of female referees in their countries. When we analysed the literature (Kane and Stangl, 1991;Norman, 2010;Passero et al, 2019;Sartore and Cunningham, 2007) we see similar results. It has suggested that women have been marginalized, discriminated against and undervalued in workplace leadership positions in sports.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Of particular note that one of the major limitations in reaching conclusions was the lack of longitudinal articles showing the evolution of the different aspects analyzed. The effects of the implementation of co-education should be observed over time, among others, by reducing sports drop-out rates and occupying leadership positions in sports that are mostly occupied by the male gender [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Internacionalmente, há pesquisas envolvendo o estudo de gênero e a representatividade em comissões técnicas de clubes esportivos, profissionais ou não, e também, em programas esportivos em universidades, demonstrando grande discrepância entre os resultados observados coletados envolvendo a diferença entre a presença de homens e mulheres (Fasting & Pfister, 2000, Cunningham & Sagas 2002Shaw & Frisby, 2006, Kilty, 2006, Reade, Rodgers & Norman, 2009, Kamphoff, Armentrout & Driska, 2010, Norman, 2010, Peachey & Burton, 2011, Burton, 2015, Fasting, Sand & Nordstrand, 2017. A nível nacional, algumas pesquisas recentes envolvendo algumas modalidades esportivas, como o caso do Handebol (Silva, Jacó & Krahenbühl, 2021) e Futebol (Passero et al, 2020) e Basquetebol (Passero et al, 2019) destacam-se, além de estudos envolvendo mulheres e o esporte de maneira geral (Goellner, 2005, 2007, Ferreira et al, 2013, Balardin et al, 2018, Ramos, 2018, Torga, 2019 (Paraná Esporte, 2021). Durante a coleta de dados, todos os cargos da Secretaria do Esporte e do Turismoórgão responsável pela competição na épocaeram ocupados por homens (Secretaria do Esporte e do Turismo, 2018).…”
Section: Introductionunclassified